The Royal Navy and the war at sea 1914-1919 - Mace, Martin; Grehan, John (Despatches from the front, 2014)
Germany's attempts to build a battleship fleet to match that of the United Kingdom, the dominant naval power on the 19th-century and an island country that depended on seaborne trade for survival, is often listed as a major reason for the enmity between those two countries that led to the outbreak of war in 1914. Indeed, German leaders had expressed a desire for a navy in proportion to their military and economic strength that could free their overseas trade and colonial empire from dependence on Britain's good will, but such a fleet would inevitably threaten Britain's own trade and empire. Despite this backdrop of large standing navies, naval warfare in the First World War was mainly characterized by the efforts of the Allied powers, with their larger fleets and surrounding position, to blockade the Central Powers by sea, and the efforts of the Central Powers to break that blockade or to establish an effective blockade of the UK with submarines and raiders. Indeed, the use of the former saw naval conflict enter a new era, one that affected every member of the British population and, in 1917, raised the spectre of a German victory.